2019
DOI: 10.3389/fpsyt.2019.00704
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Laboratory Evidence for the Abuse Potential of Tramadol in Humans

Abstract: Background: Tramadol is an opioid-analgesic that has shown epidemiological evidence of abuse. This review evaluates the evidence for tramadol abuse potential in humans. Methods: A systematic literature search for human abuse liability examinations of tramadol was conducted in September 2018 and yielded 13 total studies. Studies were all within-subject, double-blind, placebo-controlled human laboratory comparisons of tramadol to opioid comparators. Results are organized based upon the route of tramadol administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 62 publications
5
40
0
Order By: Relevance
“…Depending on the method of estimation, NMU rates of comparator opioids were up to 6.5-fold higher than NMU rates of tramadol. The relative lower rate of tramadol NMU and tramadol diversion found in this study supports that of previously published real-world data in the post-market setting from independent data sources [12,16,[20][21][22][23][24]. In one of the most recent studies [20], drug utilization-adjusted rates of tramadol intentional abuse exposures collected by poison centers were the second lowest of the opioids studied (hydrocodone 0.020 exposures/100,000 units dispensed, tramadol 0.022 exposures/100,000 units dispensed, morphine 0.052 exposures/100,000 units dispensed, and oxycodone 0.166 exposures/100,000 units dispensed); tramadol drug diversion rates were significantly lower than all other opioids studied with the exception of tapentadol, which had a similar rate (tramadol 0.047 exposures/100,000 units dispensed, hydrocodone 0.132 exposures/100,000 units dispensed, oxycodone 0.272 exposures/100,000 units dispensed, and morphine 0.274 exposures/100,000 units dispensed); and past 30-day 'to get high' rates of tramadol from a substance abuse treatment center program were significantly lower than all other opioids studied (tramadol 0.036 exposures/100,000 units dispensed, hydrocodone 0.166 exposures/100,000 units dispensed, oxycodone 0.337 exposures/100,000 units dispensed, and morphine 1.085 exposures/100,000 units dispensed).…”
Section: Discussionsupporting
confidence: 91%
“…Depending on the method of estimation, NMU rates of comparator opioids were up to 6.5-fold higher than NMU rates of tramadol. The relative lower rate of tramadol NMU and tramadol diversion found in this study supports that of previously published real-world data in the post-market setting from independent data sources [12,16,[20][21][22][23][24]. In one of the most recent studies [20], drug utilization-adjusted rates of tramadol intentional abuse exposures collected by poison centers were the second lowest of the opioids studied (hydrocodone 0.020 exposures/100,000 units dispensed, tramadol 0.022 exposures/100,000 units dispensed, morphine 0.052 exposures/100,000 units dispensed, and oxycodone 0.166 exposures/100,000 units dispensed); tramadol drug diversion rates were significantly lower than all other opioids studied with the exception of tapentadol, which had a similar rate (tramadol 0.047 exposures/100,000 units dispensed, hydrocodone 0.132 exposures/100,000 units dispensed, oxycodone 0.272 exposures/100,000 units dispensed, and morphine 0.274 exposures/100,000 units dispensed); and past 30-day 'to get high' rates of tramadol from a substance abuse treatment center program were significantly lower than all other opioids studied (tramadol 0.036 exposures/100,000 units dispensed, hydrocodone 0.166 exposures/100,000 units dispensed, oxycodone 0.337 exposures/100,000 units dispensed, and morphine 1.085 exposures/100,000 units dispensed).…”
Section: Discussionsupporting
confidence: 91%
“…Due to the metabolic delay in formation of M1, tramadol is considered an atypical opioid with less abuse liability than conventional opioids. 2,3 Oral tramadol was approved by the Food and Drug Administration (FDA) in 1995 for moderate to moderately severe pain in adults. Oral tramadol is a Schedule IV controlled substance versus other opioids which are Schedule II controlled substances in the U.S.…”
Section: Introductionmentioning
confidence: 99%
“…The scheduling difference reflects the understanding that tramadol does not carry the same abuse potential as Schedule II opioids, as supported by studies that have shown that the human abuse potential of tramadol appears to be different from and lower than other opioid analgesic medications. 2,3 However, some have been calling federal governing bodies to consider reclassifying tramadol based on observational studies 4,5 suggesting that patients receiving tramadol had similar to somewhat higher risks of prolonged opioid use compared with those receiving other short acting opioids. Those studies did not evaluate if persistent treatment for pain may be the driver for continued use, if physicians choose to prescribe tramadol due to its known less abuse potential; or if misuse or abuse was actually responsible for continued use (which, ultimately, is the key question relating when assessing abuse risk).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary advantage of tramadol, a Schedule IV controlled substance, over Schedule II opioids is that it carries less abuse liability [ 3 – 5 ], an important consideration in the context of the ongoing opioid epidemic in the US. There is a strong body of evidence that tramadol carries low but not zero abuse potential and that its abuse potential is lower than conventional opioid analgesic medications [ 6 ].…”
Section: Introductionmentioning
confidence: 99%